EFFECTS OF CYTOCHALASIN B ON THE RESPONSE OF TOAD URINARY BLADDER TO VASOPRESSIN - Davis, Walter L. (The Rockefeller University Press, 1974)
A combined physiological and morphological study of the effects of cytochalasin B (CB) on the toad urinary bladder has been carried out. CB inhibits the hydro-osmotic response to vasopressin without altering basal water permeability or diffusion, or the increase in (3)H(2)O diffusion observed after hormone addition. Although CB increases [(22)Na]-, [(36)Cl]-, and [(14)C]urea fluxes, and decreases transepithelial potential, no alteration in basal short-circuit current, the vasopressin-induced increase in this parameter, or [(14)C]inulin permeability occurs. In the absence of hormone, CB does not markedly alter the structure of the toad bladder. However, in the presence of vasopressin, CB induces the formation of large intracellular vacuoles. These results suggest a possible coupling of solute and water movement across the tissue.